Use of the superficial inferior epigastric vein in breast reconstruction with a deep inferior epigastric artery perforator flap - Varnava, Charalampos; Wiebringhaus, Philipp; Kampshoff, David; Hirsch, Tobias; Kueckelhaus, Maximilian (Frontiers in Surgery, 2023)
Background: Autologous breast reconstruction is highly regarded in reconstructive surgery after mastectomy. DIEP flap reconstruction represents the gold standard for autologous breast reconstruction. The major advantages of DIEP flap reconstruction are its adequate volume, large vascular caliber and pedicle length. Despite reliable anatomy, there are procedures where the plastic surgeon's creativity is required, not only to shape the new breast, but also to overcome microsurgical challenges. An important tool in these cases is the superficial epigastric vein (SIEV). Methods: 150 DIEP flap procedures performed between 2018 to 2021 were retrospectively evaluated for SIEV use. Intraoperative and postoperative data were analyzed. Rate of anastomosis revision, total and partial flap loss, fat necrosis and donor site complications were evaluated. Results: In a total of 150 breast reconstructions with a DIEP flap performed in our clinic, the SIEV was used in 5 cases. The indication for using the SIEV was to improve the venous drainage of the flap or as a graft to reconstruct the main artery perforator. Among the 5 cases, no flap loss occurred. Conclusions: Use of the SIEV is an excellent method to expand the microsurgical options in breast reconstruction with DIEP flap surgery. It provides a safe and reliable procedure to improve venous outflow in cases of inadequate outflow from the deep venous system. The SIEV could also provide a very good option for fast and reliable application as an interposition device in case of arterial complications.